Mechanism of mRNA Transport in the Nucleus - Diana Y. Vargas; Arjun Raj; Salvatore A. E. Marras; Kramer, Fred Russell; Tyagi, Sanjay (Proceedings of the National Academy of Sciences - PNAS, 2005)
The mechanism of transport of mRNA-protein (mRNP) complexes from transcription sites to nuclear pores has been the subject of many studies. Using molecular beacons to track single mRNA molecules in living cells, we have characterized the diffusion of mRNP complexes in the nucleus. The mRNP complexes move freely by Brownian diffusion at a rate that assures their dispersion throughout the nucleus before they exit into the cytoplasm, even when the transcription site is located near the nuclear periphery. The diffusion of mRNP complexes is restricted to the extranucleolar, interchromatin spaces. When mRNP complexes wander into dense chromatin, they tend to become stalled. Although the movement of mRNP complexes occurs without the expenditure of metabolic energy, ATP is required for the complexes to resume their motion after they become stalled. This finding provides an explanation for a number of observations in which mRNA transport appeared to be an enzymatically facilitated process.